KEMAMPUAN MENGANALISIS KESALAHAN PENGGUNAAN PREPOSISI PADA KARANGAN NARASI SISWA KELAS XI SMK NEGERI 1 SIPISPIS TAHUN AJARAN 2022-2023 - Siti Rohani Purba; Abdullah Hasibuan (Jurnal Inovasi Penelitian, 2023)
This study describes errors in the use of prepositions in essays by class XI students of SMK Negeri 1 Sipispis for the 2022-2023 academic year. The research method used in this research is a quantitative descriptive method. Data collection techniques used were written tests and documentation. The prepositions that are the subject of discussion in this study are as many as 6 prepositions, which include in, to, from, by, for, and to. The results of this research show that there are 326 prepositions used. The prepositions include 94 prepositions di, 167 prepositions to, 22 prepositions of, 5 prepositions by, 34 prepositions for, and 4 prepositions to. There were 130 prepositions that were not used correctly in the essays made by students. 96 of these prepositions included in and 34 used the preposition to.